Pengaruh Lingkungan Kerja, Gaya Kepemimpinan, dan Hubungan Informal di Tempat Kerja Terhadap Turnover Karyawan PT Aseli Dagadu Jokdja - Asmiyati, Asmiyati; Rahayu, Meika Kurnia Puji (Universitas Muhammadiyah Yogyakarta, 2020)
This study aims to analyze the influence of work environment, leadership style, and informal relationships in workplace to employee turnover intention in PT Aseli Dagadu Djokdja. The subjects in this study were employee of PT Aseli Dagadu Djokdja. In this study, 80 questionnaires were distributed, and only 72 questionnaires could be processed using purposive sampling techniques. The data obtained is then processed using multiple linear regression analysis with software of SPSS 22.0. Based on the analysis that has been done, the results show that work environment have a significant negative effect on turnover intention and the results show that informal relationships in workplace have a significant positive effect on turnover intention. While the variables of leadership style do not have a positive effect on turnover intention.